Effect of Ethanol-Derived Clove Leaf Extract on the Oxidative Stress Response in Yeast Schizosaccharomyces pombe - Anninda Faiz Fauzya; Rika Indri Astuti; Nisa Rachmania Mubarik (International Journal of Microbiology)
Compared to the widely explored antioxidant activity from the clove bud extract, less data are available regarding the potential pharmacological use of clove leaves. Our study aimed to explore the antioxidant activity of clove leaves extract in the cellular level. Thus, we used the yeast Schizosaccharomyces pombe as model organisms. Our data indicate that, following extract treatment (100 ppm), the viability of the stationary phase cells of S. pombe was higher than without extract and that of calorie restriction treatments. 100 ppm extract treatment also increased cell viability against H2O2-induced oxidative stress. Those data indicate that the extract could promote oxidative stress tolerance response in yeast cells, which occurred either during the stationary phase or due to exogenous exposure. Higher dose of extract (500 ppm) showed opposite effects, as cell viability was lower than that without treatment. Analysis toward the mitochondrial activity revealed that the extract did not induce mitochondrial activity unlike the calorie restriction treatment. Based on our data, clove leaf extract promotes oxidative stress tolerance response in the yeast S. pombe, independent to that mitochondrial adaptive ROS signaling which commonly occurs in calorie restriction-induced oxidative stress tolerance response.